2014
DOI: 10.1016/j.molonc.2014.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Dying tumor cells stimulate proliferation of living tumor cells via caspase‐dependent protein kinase Cδ activation in pancreatic ductal adenocarcinoma

Abstract: Pancreatic cancer is one of the most lethal human cancers, and radiotherapy is often implemented for locally advanced pancreatic ductal adenocarcinoma. Tumor cell repopulation is a major challenge in treating cancers after radiotherapy. In order to address the problem of tumor repopulation, our previous studies have demonstrated that dying cells stimulate the proliferation of living tumor cells after radiotherapy. In particular, dying cells undergoing apoptosis also activate survival or proliferation signals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 36 publications
4
68
0
Order By: Relevance
“…Dying pancreatic cancer cells after radiotherapy can act as feeder cells for living tumor cells. It was shown that this is mediated by a Caspase 3/PKCδ signaling pathway that is active in dying tumor cells [21]. …”
Section: Targeting Pkcε Pkcδ or Downstream Signaling In Pancreatic Cmentioning
confidence: 99%
“…Dying pancreatic cancer cells after radiotherapy can act as feeder cells for living tumor cells. It was shown that this is mediated by a Caspase 3/PKCδ signaling pathway that is active in dying tumor cells [21]. …”
Section: Targeting Pkcε Pkcδ or Downstream Signaling In Pancreatic Cmentioning
confidence: 99%
“…These findings were validated in breast cancer, melanoma, and pancreatic ductal adenocarcinoma cell lines (Cheng et al, 2015; Donato et al, 2014; Kurtova et al, 2015). …”
Section: Apoptotic Cells Directly Influence Tissue Homeostasis Andmentioning
confidence: 65%
“…In addition to the Caspase-3/iPLA 2 /PGE 2 signaling, in certain cancer cell lines such as the Panc1 line derived from ductal carcinoma, there is also a role for 7-PKCδ-Akt/p38 MAPK-stimulated mitogen production (Cheng et al, 2015). Also, there is evidence of Sonic Hedgehog modulating AiP, feeding back on dying cells in a paracrine manner to regulate WNT signaling via SFRP1 (secreted frizzled related protein 1).…”
Section: Apoptotic Cells Directly Influence Tissue Homeostasis Andmentioning
confidence: 99%
“…PKCδ has been shown to drive anchorage-independent growth through activation of the PI3K-Akt pathway, and treatment of Panc1 cells overexpressing PKCδ with the PI3K inhibitor LY294002 prevented soft agar colony formation [64]. Besides its roles in cell survival, anchorage independent growth and proliferation, PKCδ is also implicated in cell metastasis [82], and overexpression of PKCδ enhances the metastatic capability of Panc1 cells in xenografts [64]. …”
Section: Pkc In Pancreatic Cancermentioning
confidence: 99%
“…Ionizing radiation causes cleavage and activation of caspases 3 and 7, of which caspase 3 cleaves PKCδ, resulting in an active, unregulated kinase fragment [95, 96]. This active PKCδ fragment then activates Akt to drive tumor cell proliferation [82]. While PKCε can be activated by caspase 3 by a similar mechanism, it so far has not been implicated in this pathway [96].…”
Section: Pkc In Pancreatic Cancermentioning
confidence: 99%